Varietal Response of Wheat to Different Levels of Nitrogen in Agri- Horticulture System Under Rainfed Hill Farming System - Verma, K.S.; Sood, R.; Kaushal, R. (Indian Journal of Agroforestry, 2020)
Growth and yield response of four wheat varieties with three nitrogen levels in 12 years old peach based agri-horticulture system was studied. Plant growth attributes viz. germination per cent, number of plants m-2 and number of tillers plant-1 were not influenced significantly albeit, plant height increased significantly with the 25 % increase in N level (N3 Varietal effects were significant. The yield attributes viz. number of spikes per plant, thousand grain weight, straw and grain yield as well as harvest index were influenced significantly by N -levels. The direction of crop sowing also had significant effect on yield attributes. Grain yield was higher in south direction over north. Grain yield in Agri-horti system compared to sole crop system was 18.45 per cent less with recommended level of N2. Increase in N by 25 % over recommended level (N2) improved the yield by 3.35 % in AH system. Reduction in N level by 25 % over recommended level, decreased the yield in AH system by 25.27 per cent, whereas, in sole crop just by 4.70%. Variety V3 (HD-2380) produced maximum grain yield (22.17 q ha-1) in AH and (26.00 q ha-1) in sole crop system. Net returns from AH system were higher (Rs. 43424.14) compared to sole crop (Rs. 26876.73) at N3V3Â combination. Hence, in Peach based agri-horticulture system, use of variety HD-2380 with 100 kg N ha-1 would be a viable option to obtain higher yield and higher net returns.